Removal of Metal Ions and Organic Compounds from Aqueous Environments Using Versatile Carbon Nanotube/Graphene Hybrid Adsorbents. Issue 1752 (2014) - Dichiara, Anthony B.; Webber, Michael R.; Rogers, Reginald E.
ABSTRACT: The contamination of water by a large variety of molecules is a major environmental issue that will require the use of efficient and versatile materials to purify hydrological systems from source to point-of-use. The present study describes the aqueous-phase adsorption of heavy metal ions and multiple organic compounds at environmentally relevant concentrations onto graphene-single-walled carbon nanotube free-standing hybrid papers. Optical absorption spectroscopy results clearly showed that the hybrid nanocomposites exhibit superior adsorption properties compared to activated carbon, the most widely used adsorbent to date.